Non-invasive Technology for Monitoring of Cerebrovascular Autoregulation - Ragauskas, A.; Daubaris, G.; Petkus, V.; Raišutis, R.; Chomskis, R.; Šliteris, R.; Deksnys, V.; Guzaitis, J.; Lengvinas, G.; Rugaitis, A. (Elektronika ir Elektrotechnika, 2008)
New non-invasive ultrasonic technology for CA monitoring has been created which uses both intracranial slow wave and respiratory wave methodologies. The technology provides information about the intracranial blood volume dynamics in the smallest vessels responsible for cerebral blood flow autoregulation – small arterial vessels and arterioles. The clinical study shows that the non-invasive technology could be applied for continuous monitoring of CA by using slow intracranial wave or intracranial respiratory wave methodologies. Ill. 4, bibl. 12 (in English, summaries in English, Russian and Lithuanian).